Contrast‐induced nephropathy after cardiac resynchronization therapy implant impairs the recovery of ejection fraction in responders - Teresa Strisciuglio; Giuseppe Ammirati; Valerio Pergola; Livio Imparato; Cristina Carella; Elisabeta Koci; Rosaria Chiappetti; Fabio Giovanni Abbate; Vincenzo Mirco La Fazia; Aniello Viggiano; Bruno Trimarco; Antonio Rapacciuolo (ESC Heart Failure, 2019)
Abstract Aims Data regarding contrast‐induced nephropathy (CIN) after cardiac resynchronization therapy (CRT) implant are limited. We aimed to investigate the incidence and determinants of CIN and its impact on CRT response and outcomes. Methods and results Patients who underwent CRT implant were retrospectively analysed, and CIN was defined as an increase of serum creatinine ≥0.3 mg/dL or ≥1.5 times the baseline value. Response to CRT was defined as a reduction of left ventricle end‐systolic volume (LVESV) of 15% or the increase of five percentage points in ejection fraction (EF) as assessed by echocardiography at 6 months. Follow‐up visits were scheduled at 3, 6, and 12 months. Contrast‐induced nephropathy occurred in 13/107 patients (12%). Among baseline clinical, echocardiographic, and laboratory characteristics, only a high baseline serum creatinine was associated with the occurrence of CIN. Symptoms, EF, and LVESV at 6 months improved in both CIN and non‐CIN patients, and the rate of responders to CRT was similar. Among responders, at 6 months, those with CIN had significantly lower EF (28.5% vs. 35.7% P = 0.003). At a median follow‐up of 112 weeks, 43% of patients experienced a clinical event with similar incidence in CIN and non‐CIN patients, and likewise survival was similar. Non‐responders to CRT had worse survival while among responders those with CIN had worse survival than non‐CIN patients (71% vs. 90%, P = 0.0035). Conclusions The incidence of CIN is rather high. Although CIN does not influence response to CRT overall, however among responders impairs the recovery of EF and survival.